Bisphenol A and its analogues: A comprehensive review to identify and prioritize effect biomarkers for human biomonitoring. (November 2020) - Mustieles, Vicente; D'Cruz, Shereen Cynthia; Couderq, Stephan; Rodríguez-Carrillo, Andrea; Fini, Jean-Baptiste; Hofer, Tim; Steffensen, Inger-Lise; Dirven, Hubert; Barouki, Robert; Olea, Nicolás; Fernández, Mariana F.; David, Arthur
Highlights: This review identified and prioritized existing effect biomarkers for bisphenols. 119 epidemiologic studies were selected, analyzed, tabulated and discussed. An inventory of molecular and biochemical effect biomarkers was created. BDNF, kisspeptin and gene expression of nuclear receptors were prioritized. Adverse outcome pathway (AOP) data was gathered to cover knowledge gaps. Abstract: Human biomonitoring (HBM) studies have demonstrated widespread and daily exposure to bisphenol A (BPA). Moreover, BPA structural analogues (e.g. BPS, BPF, BPAF), used as BPA replacements, are being increasingly detected in human biological matrices. BPA and some of its analogues are classified as endocrine disruptors suspected of contributing to adverse health outcomes such as altered reproduction and neurodevelopment, obesity, and metabolic disorders among other developmental and chronic impairments. One of the aims of the H2020 European Human Biomonitoring Initiative (HBM4EU) is the implementation of effect biomarkers at large scales in future HBM studies in a systematic and standardized way, in order to complement exposure data with mechanistically-based biomarkers of early adverse effects. This review aimed to identify and prioritize existing biomarkers of effect for BPA, as well as to provide relevant mechanistic and adverse outcome pathway (AOP) information in order to cover knowledge gaps and better interpret effect biomarker data. A comprehensive literature search was performed in PubMed to identify all the epidemiologic studies published in the last 10 years addressing the potential relationship between bisphenols exposure and alterations in biological parameters. A total of 5716 references were screened, out of which, 119 full-text articles were analyzed and tabulated in detail. This work provides first an overview of all epigenetics, gene transcription, oxidative stress, reproductive, glucocorticoid and thyroid hormones, metabolic and allergy/immune biomarkers previously studied. Then, promising effect biomarkers related to altered neurodevelopmental and reproductive outcomes including brain-derived neurotrophic factor (BDNF), kisspeptin (KiSS), and gene expression of nuclear receptors are prioritized, providing mechanistic insights based on in vitro, animal studies and AOP information. Finally, the potential of omics technologies for biomarker discovery and its implications for risk assessment are discussed. To the best of our knowledge, this is the first effort to comprehensively identify bisphenol-related biomarkers of effect for HBM purposes.